Answer:
4
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
6−4x=6x−8x−2
6+−4x=6x+−8x+−2
−4x+6=(6x+−8x)+(−2)(Combine Like Terms)
−4x+6=−2x+−2
−4x+6=−2x−2
Step 2: Add 2x to both sides.
−4x+6+2x=−2x−2+2x
−2x+6=−2
Step 3: Subtract 6 from both sides.
−2x+6−6=−2−6
−2x=−8
Step 4: Divide both sides by -2.
−2x−2=−8−2
x=4
here is a link:
https://www.mathpapa.com/algebra-calculator.html?q=6-4x%3D6x-8x-2.
Answer:
y= -1/2x+5 , y= -4x -2
Step-by-step explanation:
im not very sure
Answer:
Step-by-step explanation:
Hope this helps!
Answer:
Hello, Friend! ^^
The Answer Is 13 Inches <3
_______________________________________________________
Hope this helps! ^^ :3
Answer:
Yes
Step-by-step explanation:
Many students gets confused with these exponential problems, they often get misguided but understand that there is nothing to be confused of.
When you have a negative number, you just take the reciprocal of the whole exponent number.
What is a reciprocal?
Let's take an integer for example, let's take the number 3.
The reciprocal for 3 is (1/3)
Let's take an other number, let's take 2/3
The reciprocal for 2/3 is (3/2)
In conclusion, we just reverse the denominator and the numerator or just switch it.
We take 3 as (3/1) and that is the reason, the reciprocal would be (1/3)
Now, coming to the negative integers. Taking an example:
(2)⁻¹
This would be become (1/2¹) = (1/2)
Hence, the result of a negative integer is positive but would be a fraction.
Hope I helped!